The drivers of women farmers' participation in cash crop production: the case of women smallholder farmers in Northern Ghana. Issue 2 (15th March 2017) - Zakaria, Hudu
ABSTRACT: Purpose : Participation in labour markets and high-value crops among men and women smallholder farmers has always been an important strategy for poverty alleviation and attainment of food and income security. In contributing to the generation of gender-disaggregated empirical literature, this paper examined determinants of women smallholder farmers' participation in their households' decision-making regarding cash crop production. Methodology: Data for the paper were sourced from a baseline survey conducted by Monitory and Evaluation Technical Support Services, Institute of Statistical, Social and Economic Research and Ghana Statistical Service for the USAID Feed the Future Programme in their Northern Ghana Zone of Influence. The data were analysed using probit regression analysis to identify factors which significantly influence women farmers' participation in cash crop production. Findings: The probit analysis identified intra-household power relations such as women participation in household decision-making, control over household productive resources and control over household income as significant determinants of smallholder women farmers' participation in cash crop production. Theoretical Implication: Improving women smallholder farmers' power to participate in household decision-making, access to and control over household productive resources and income are therefore imperative in boosting women farmers' participation in cash crop production. Practical Implications: It is therefore recommended that any gender-targeted policy and programme with the aim of women's economic empowerment must critically examine the sociocultural barriers impeding women's participation in their household decision-making and control over household productive resources. Women farmers' participation in their households' decision-making regarding cash crop production and the use of income generated from it should be encouraged through gender mainstreaming in agricultural service delivery.